Reexamining Karl Barth’s Concept of Evil Death through the Lens of Apocalyptic Framework - Tin, Tsz-fung (Journal of reformed theology, 2025)
Despite the extensive studies on Karl Barth’s theology, the concept of death in Barth’s work has not received significant attention within current Barth scholarship. Nevertheless, given the growing recognition of the apocalyptic elements within Barth’s theology in recent years, it is important to explore the apocalyptic characteristics of Barth’s conception of ‘evil death,’ an aspect that has not been thoroughly examined. This essay aims to address this gap by examining the apocalyptic elements present in Barth’s view of ‘evil death’ as outlined in Church Dogmatics (CD) § 47.5 and to evaluate two criticisms directed at Barth’s concept of death.